Avaliação tomográfica da reabsorção radicular apical e das alterações no tecido periodontal de suporte induzidas pelo aparelho Herbst - Schwartz, João Paulo [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Abstract This study evaluated quantitatively, alveolar bone height and thickness in the central and lateral lower incisors and apical root resorption in all roots after using Herbst appliance. The sample comprised 23 patients (11 men, 12 women), mean ages 15.76 ± 1.75 years, presenting class II division 1, treated with Herbst appliance. Cone-beam computed tomography (CBCT) images were obtained before and after Herbst treatment. The vertical alveolar bone level and the alveolar bone thickness of lower incisors were assessed. Vestibular (V), lingual (L) and total (T) bone thicknesses were assessed at the crestal (1), midroot (2) and apical (3) levels of the lower incisors. The apical root resorption was determined using axial guided navigation of CBCT images. The Student’s t-Test and Wilcoxon t-Test were used to compare dependent samples in parametric and non-parametric cases, respectively. The results were considered at a significance level of 5%. The lower incisors showed no statistical significance for the vertical alveolar bone level. The alveolar bone thickness of lower incisors significantly reduced after the treatment at V1, V2, V3, T1 and significantly increased at L2. Apical root resorption was detected by CBCT in 57.96% of 980 roots that underwent treatment. The CBCT, for allowing three-dimensional evaluation of dental roots, showed that Herbst appliance induces mild apical root resorption, mostly in the anchoring teeth, and the tooth movement induced by this appliance causes alveolar bone reduction on the vestibular side of lower incisors.

Este estudo avaliou quantitativamente altura e espessura óssea alveolar nos incisivos centrais e laterais inferiores e reabsorção radicular apical em todas as raízes, após uso do aparelho Herbst. Amostra composta por 23 indivíduos brasileiros (11 gênero masculino e 12 gênero feminino), média de idade 15,76 ± 1,75, má oclusão Classe II divisão 1, tratados com Herbst. Tomografias computadorizadas de feixe cônico (TCFC) foram realizadas antes e após o tratamento com Herbst. A altura e a espessura óssea alveolar dos incisivos inferiores foram avaliadas. As espessuras ósseas vestibular (V), lingual (L) e total (T) foram mensuradas nos terços cervical (1), médio (2) e apical (3) dos incisivos inferiores. A reabsorção radicular apical foi determinada pelo método da navegação axial guiada nas imagens de TCFC. O Teste t de Student e o Teste T de Wilcoxon compararam as amostras dependentes nos casos paramétricos e não paramétricos, respectivamente. Os resultados foram considerados para um nível de significância de 5%. Os incisivos inferiores não apresentaram diferença estatística significante para a altura óssea alveolar. A espessura óssea alveolar dos incisivos inferiores reduziu significativamente após o tratamento em V1, V2, V3, T1 e aumentou em L2. A reabsorção radicular apical foi detectada pela TCFC em 57,96% das 980 raízes avaliadas. A TCFC, por permitir a avaliação tridimensional das raízes dentárias, demonstrou que o aparelho Herbst induz reabsorção radicular apical suave, principalmente nos dentes de ancoragem, e o deslocamento dentário induzido por esse aparelho causa redução da espessura óssea alveolar vestibular nos incisivos inferiores.
Keywords: Tomografia Computadorizada de Feixe Cônico; Periodonto; Ortodontia; Periodontium